Pengaruh vermikompos dan tipe lahan tanah grumusol terhadap pertumbuhan dan serapan nitrogen jagung manis - Rr Naura Rachma Pramesti; Parwi Parwi (Universitas Djuanda, 2026)
Grumusol soil has considerable potential for crop cultivation; however, its productivity is often constrained by unfavorable physical and chemical properties. This study evaluated the effects of different vermicompost sources and Grumusol soils from two land-use types on the growth and nitrogen (N) uptake of sweet corn (Zea mays L.). A two-factor factorial Completely Randomized Design (CRD) with three replications was employed. The first factor comprised four vermicompost treatments: no vermicompost (control), chicken manure vermicompost, cattle manure vermicompost, and market waste vermicompost. The second factor was Grumusol soil collected from paddy fields and dryland. Plant height, leaf number, stem diameter, fresh biomass, dry biomass, and nitrogen uptake were measured. Data were analyzed using analysis of variance, followed by the Least Significant Difference (LSD) test at the 5% significance level. Vermicompost source significantly affected plant height at 35 days after planting (DAP) and nitrogen uptake. Market waste vermicompost produced the highest nitrogen uptake, whereas cattle manure and market waste vermicomposts resulted in greater plant height at 35 DAP than the other treatments. Grumusol soil origin significantly affected plant height, stem diameter, fresh biomass, dry biomass, and nitrogen uptake but had no significant effect on leaf number. Sweet corn grown in Grumusol soil from dryland exhibited superior vegetative growth and nitrogen uptake compared with plants grown in Grumusol soil from paddy fields. These findings suggest that market waste vermicompost, particularly when applied to Grumusol soil from dryland, can serve as an effective nutrient management strategy for improving sweet corn growth and nitrogen uptake.